Mapping the Literature of Financial Management Behavior:A Bibliometric Analysis (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The publication of financial management behavior research has grown gradually, and the tendencies have been persistently improving.Nevertheless, there is a need to provide an in-depth scientific analysis of the field. Because of this, the study uses knowledge structure synthesis to try and identify the trend in the research field.A Bibliometric analysis of financial management behaviour was carried out. The Scopus database was used to compile literature on financial management behaviour from 1969 through 2022. The study selected 389 valid documents for further examination based on the 'keywords' search results.Out of 389 publications, 322 are Articles, 27 Book Chapters, 27 Conference Papers, 11 Reviews, one Book, and one Letter.The authors then used Biblioshiny R package to visualize the data. Results reveal that from 2007 until the present, there has been a rise in the literature on financial management behaviour. However, in 2013, the figure was slightly lower.